Pengaruh Risiko Perusahaan Terhadap Nilai Perusahaan (Studi pada Perusahaan Subsektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Puspitasari, Ayu; Damayanti, Damayanti; Harori, Muhammad Iqbal (Jurnal Kompetitif Bisnis, 2024)
This study aims to determine the effect of corporate risk, which consists of business risk, financial risk, and market risk variables on firm value in consumer goods industry sub-sector companies listed on the Indonesia Stock Exchange in 2014-2018. The analytical method used in this study is multiple regression analysis of panel data models using the E-viwes 11 analysis tool. The data used in this study are secondary data consisting of annual financial reports and stock prices for the years 2014-2018 for each research variable. . The results of this study indicate that partially the market risk variable has a positive and significant effect on the firm value variable. Meanwhile, partially the business risk and financial risk variables have a positive and insignificant influence on the firm value variable. Furthermore, simultaneously it shows that the variables business risk, financial risk and market risk have a positive and significant influence on the variable firm value.